Anti-obesity effects of Celastrus orbiculatus extract containing celastrol on canine adipocytes - Kim, Cho-Won (Can J Vet Res, 2021)
From 50 to 60% of companion animals in the United States are overweight or obese and this obesity rate is rising. As obesity is associated with a number of health problems, an agent that can help weight loss in pets and assist in clinically managing obesity through veterinary prescription foods and medication would be beneficial. Many studies have shown that celastrol, a phytochemical compound found in Celastrus orbiculatus extract (COE), has anti-obesity and anti-inflammatory effects, although these effects have not yet been determined in canine or canine-derived cells. The objective of this study was to investigate the effects of celastrol on the adipogenic differentiation and lipolysis of canine adipocytes. Primary preadipocytes were isolated from the gluteal region of a beagle dog and the primary adipocytes were differentiated into mature adipocytes by adipocyte differentiation media containing isobutylmethylxanthine, dexamethasone, and insulin. In a water-soluble tetrazolium (WST) assay, the cell viability of mature adipocytes was decreased after treatment with COE (0, 0.93, 2.32, and 4.64 nM celastrol) in a concentration-dependent manner, although preadipocytes were not affected. Oil Red O (ORO) staining revealed that COE inhibited the differentiation into mature adipocytes and lipid accumulation in adipocytes. In addition, treatment with COE significantly reduced triglyceride content and increased lipolytic activities by 1.5-fold in canine adipocytes. Overall, it was concluded that COE may enhance anti-obesity activity in canine adipocytes by inhibiting lipid accumulation and increasing lipolytic activity.